Open access essentials: how you can go open access with CIAT? - Rajasekharan, Maya; Gil, L.; Jaramillo, MV; Saa, C; Staiger Rivas, Simone; Zandstra, Megan (2014)
What is Open Access? Are you uncertain as to what it’s all about and what you can you do to enhance access to your research results? This seminar will give you an overview and update of CGIAR and CIAT’s open access policy, legal context, issues and considerations related to open access, progress made in managing different types of data and further opportunities and plans to strengthen open access in CIAT. There will be time for discussion where we look forward to hear your suggestions and experiences related to open access.